A new signcryption algorithm for secure communication in ad hoc networks. (7th April 2021) - Li, Shanshan
Mobile ad hoc network is a self-organised network formed by mobile nodes. Due to the unique structure of mobile ad hoc network, the conventional security scheme cannot be applied. In this paper, a new signcryption algorithm for secure communication in ad hoc network is studied. On the basis of identity based signcryption algorithm, we introduce the logical layout of the grid, assign ID to each node according to the grid vertex. The key management scheme using the algorithm also has lower operation cost and communication cost, which is more suitable for the security requirements of ad hoc network. The experimental results show that the improved protocol can effectively resist two kinds of man in the middle attacks, and for our enhanced man in the middle attacks with unlimited computing power, it can still effectively resist, showing good performance.